Procedure and experience of implementing One Health field sites at the grassroots level in Lao PDR and similar contexts - Pham Duc Phuc; Unger, Fred (International Livestock Research Institute, 2024)
The One Health (OH) approach promotes collaboration across human, animal, and environmental health sectors to address zoonotic diseases and other health challenges. This brief explores the process of establishing a grassroots OH field site in Lao PDR as part of the "One Health Training on Enhancing Integrated Approaches to Control Zoonoses in Southeast Asia," held in Vientiane on October 29–30, 2024. The initiative aimed to strengthen cross-sectoral collaboration and offer localized solutions for zoonotic disease prevention and control. Key procedures included stakeholder engagement, capacity building, site selection, and community involvement. The field site activities focused on integrated disease surveillance, vaccination drives, and environmental health improvements. The experiences and lessons learned highlighted the importance of strong leadership, community involvement, and university collaboration in implementing successful OH strategies. Challenges such as resource limitations and stakeholder coordination were identified, with recommendations for scaling up and enhancing OH field sites in Southeast Asia. The establishment of this field site demonstrated the potential for grassroots initiatives to significantly contribute to managing zoonotic diseases and advancing the One Health agenda.